Perceived Benefits of Automation and Artificial Intelligence in the AEC Sector: An Interpretive Structural Modeling Approach - Onososen, Adetayo Olugbenga; Musonda, Innocent (Frontiers in Built Environment, 2022)
Increasing demand for infrastructure amidst the surge in the urbanization of cities and newly emerging commercial nerves has spurred the need to reinvent and rethink traditional approaches for delivering infrastructure. This has been identified as even more critical given the global drive and discourse on the sustainability of the construction sector and its health and safety performance. Given the potential gains of adopting construction automation and AI in infrastructure delivery, stakeholders’ convincing appreciation of its benefit is vital to its widespread adoption in the AEC sector. This explored and evaluated the critical benefits of integrating automation in construction processes in the architectural, engineering, and construction sector and the use of artificial intelligence (AI) in driving its systems and workflows. The study adopts an interpretive structural modeling approach based on interviews of construction stakeholders in diverse countries to develop a hierarchical model of the interrelationships of the benefits. Furthermore, the Matrice d’Impacts croises-multiplication applique a classement analysis (MICMAC) was used to categorize the benefits. Highlighted perceived benefits such as improved project quality, simplification of construction tasks, workflow improvements, and safety performance, amongst others, were fractionalized into levels. The study’s findings are critical in satisfying a cost-benefit index of adopting automation and AI in the AEC sector. The results provide recommendations on effective approaches pivotal to driving automation and AI for practice and research. This is of further importance to construction stakeholders, policymakers, and local authorities in building strategies and roadmaps for proper integration of these systems and widespread adoption.